THE PROVISION OF WILLIAM'S FLEXION EXERCISE IS BETTER THAN MULLIGAN TECHNIQUES WITH INFRARED INTERVENCE COMBINATION IN IMPROVING THE RANGE OF LUMBOSACRALMOTION OF NON-SPECIFIC LOW BACK PAIN PATIENTS - Nirmala, I Gusti Ayu Surya; Winaya, I Made Niko; Griadhi, I Putu Adiartha (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 2 (2018): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2018.v06.i02.p01, 2018)
Wearing high heels can cause a decrease in the lumbosacral ROM of the Non-spesific low back pain due to a long standing position results muscle work harder with hyperextended position. The aim of this research is to know William’s Flexion Exercise–Infrared combination is better to improve the ROM of the lumbosacral rather than Mulligan combined– Infrared combination technique, measured using Flexible Curve. The study design used in this study was experimental with pre-test design and post-test group design with 32 samples divided into two groups. Hypothesis test mean increase in ROM of the lumbosacral with Independent Sample T-test in the intervention group William’s Flexion Exercise and Mechanical Mulligan showed significant results (21.03 and 19.79) with a value of p = 0.000 (p<0.05). The result showed that the group of William’s Flexion Exercise – Infrared combination is better than the Mulligan technique. Keywords: william’s flexion exercise, mulligan technique, lumbosacral range of motion, flexible curve , non-spesific low back pain